Calagem superficial e aplicação de gesso em sistema plantio direto de longa duração: efeitos no solo e na sucessão milho/crambe/feijão-caupi - Costa, Claudio Hideo Martins da [UNESP] (2015)
Brazil has extensive area with acid soils. This areas under no-till system exists the necessity to apply soil acidity correctives materials. In the short term, the effects of superficial liming is restricted to the upper soil layers. The use of phosphogypsum is an alternative to improve the root environment in the subsurface, and can be used in acid soils as a liming supplement. However, it remains unknown how the surface application of limestone and gypsum affects the physical attributes, soil organic matter and non-traditional crops. The experiment was carried out in an experimental area, in the city of Botucatu (SP, Brazil), continuing a research project that has been conducted since 2002, to evaluate the long-term effects of surface application of lime and gypsum on chemical and physical properties, and organic matter, as well as in plant nutrition and yield components and grain yield of corn, crambe and cowpea, in the crop seasons 2010/11 and 2011/12. The experimental design was a randomized block with 4 replications. The plots were as follows: original condition and application of limestone (2.700 + 2.000 + 2.000 kg ha-1), gypsum (2.100 + 2.100 + 2.100 kg ha-1) and limestone + gypsum [(2.700 + 2.100 kg ha-1) + (2.000 + 2.100 kg ha-1) + (2.000 + 2.100 kg ha-1)], applied in October 2002, November 2004 and October 2010. As summer crop was used corn, and in the off season crambe followed by cowpea. The following evaluations were performed: chemical soil attributes at 12 and 24 months after the last application of inputs; physical fractionation of soil organic matter and soil physical attributes at 24 months after the last application of inputs; and yield components and crop yield. The surface application of limestone, with or without gypsum, were effective in reducing soil acidity to a depth of 0.20 m. The Ca2+ and Mg2+ levels in the soil increased in the surface and subsurface with liming. The Ca2+ ...